TGF-β-Induced Endothelial to Mesenchymal Transition in Disease and Tissue Engineering - Ma, Jin; Sanchez-Duffhues, Gonzalo; Goumans, Marie-José; ten Dijke, Peter (Frontiers in Cell and Developmental Biology, 2020)
Endothelial to mesenchymal transition (EndMT) is a complex biological process that gives rise to cells with multipotent potential. EndMT is essential for the formation of the cardiovascular system during embryonic development. Emerging results link EndMT to the postnatal onset and progression of fibrotic diseases and cancer. Moreover, recent reports have emphasized the potential for EndMT in tissue engineering and regenerative applications by regulating the differentiation status of cells. Transforming growth factor β (TGF-β) engages in many important physiological processes and is a potent inducer of EndMT. In this review, we first summarize the mechanisms of the TGF-β signaling pathway as it relates to EndMT. Thereafter, we discuss the pivotal role of TGF-β-induced EndMT in the development of cardiovascular diseases, fibrosis and cancer, as well as the potential application of TGF-β-induced EndMT in tissue engineering.